Dielectric Characterization of PCB Laminate Materials Using Improved Capacitive Coupled Ring Resonators - Evelyn Quinapaxi Cabrera; Aldrin Reyes Narváez; Hernan Barba Molina (Engineering Proceedings, 2023)
An improved ring resonator structure consisting of a capacitive coupling fixture is presented. Dielectric characterization is carried out using a fitting method that allows for comparison between measured and simulated results by setting a coupling level of about −4 dB and an unloaded quality factor of about 54. The key factor in this approach is the coupled energy, which permits measurements to be made well above the noise threshold. Furthermore, when applied within a frequency range, the dielectric dispersion can be studied as well. As proof-of-concept fixtures, five structures for the L-band at resonance frequencies of 1 GHz, 1.25 GHz, 1.5 GHz, 1.75 GHz, and 2 GHz are designed, manufactured, and measured. The method applied in this study provides good results as verified by error calculations.